2021
DOI: 10.1186/s12887-021-02974-9
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and clinical characteristics of multisystem inflammatory syndrome in children (MIS-C) associated with covid-19 in critically ill patients: an observational multicenter study (MISCO study)

Abstract: Background The clinical presentation and severity of Multisystem Inflammatory Syndrome in Children associated with COVID-19 (MIS-C) is widespread and presents a very low mortality rate in high-income countries. This research describes the clinical characteristics of MIS-C in critically ill children in middle-income countries and the factors associated with the rate of mortality and patients with critical outcomes. Methods An observational cohort st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
5
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 34 publications
(30 reference statements)
6
59
5
8
Order By: Relevance
“…These findings are similar to those reported for Latin America ( 9 , 14 ) but differ from those reported in the United States where about 99% of the patients had positive IgG-type serology for SARS-CoV-2 ( 19 ). This latter is in contrast to what was reported in another Colombian study where 67% of the patients had positive RT-PCR and only 13% had positive serology for SARS-CoV-2 ( 18 ).…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…These findings are similar to those reported for Latin America ( 9 , 14 ) but differ from those reported in the United States where about 99% of the patients had positive IgG-type serology for SARS-CoV-2 ( 19 ). This latter is in contrast to what was reported in another Colombian study where 67% of the patients had positive RT-PCR and only 13% had positive serology for SARS-CoV-2 ( 18 ).…”
Section: Discussioncontrasting
confidence: 97%
“…The most frequent treatment was intravenous human immunoglobulin used in 85% of the cases, followed by the use of ASA (73%). Glucocorticoids were used in 10 patients and always in combination with immunoglobulin; this is similar to what has been reported in different studies worldwide ( 9 , 14 , 18 ). Nowadays, there are no prospective studies evaluating the best therapy, but most of them have shown the effectiveness of the use of immunoglobulin, steroid, or a combination of these in the management of patients with MIS-C ( 12 , 20 ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Furthermore, Verdoni et al [ 11 ] reported a 30-fold increased risk for that Kawasaki-like disease in patients infected with SARS-CoV-2, and in the same line, they declared an increased risk of MAS and shock in patients with MIS-C. MIS-C is a rare and serious inflammatory condition associated with COVID-19. The mortality rate varies from 1% to 9% according to multicenter studies [ 12 , 13 , 14 ]. Although initial reports announced this new condition as a Kawasaki-like disease, it is well known now that patients with MIS-C may present with different system involvements.…”
Section: Discussionmentioning
confidence: 99%